Virtual reality applications in manufacturing industries: Past research, present findings, and future directions. (March 2015) - Choi, SangSu; Jung, Kiwook; Noh, Sang Do
Today, manufacturing industries are trying to improve their competitiveness by combining manufacturing per se with information technology. Virtual reality is being used in product development processes in manufacturing enterprises as a helpful technology to achieve rapid consolidation of information and decision-making through visualization and experience. In this article, 154 articles relevant to virtual reality's application to manufacturing were surveyed and analyzed. For this, (1) an analysis map was created, based on a virtual reality technology classification and the new product development process; (2) the articles investigated were located on the map; and (3) bibliometric analyses were carried out. Trends in past and present research were examined and future virtual reality research directions and application plans for manufacturing enterprises are discussed.